Sagittal Inclination Angle of the Graft Affects Graft Maturity and Knee Stability After Anterior Cruciate Ligament Reconstruction - Ming Li; Fangang Meng; Dianbo Long; Dorje Wencheng; Yanlin Zhong; Yan Kang; Peihui Wu; Aishan He (Orthopaedic Surgery)
ABSTRACT Objective The influence of the graft sagittal inclination angle (SIA) on knee stability, biomechanics, and graft maturity has been elucidated. However, no study has comprehensively described the effects of SIA on the aforementioned postoperative prognostic indicators. So, we aimed to determine whether the sagittal inclination angle (SIA) of a graft is associated with postoperative graft maturity, joint stability, and joint function after anterior cruciate ligament (ACL) reconstruction. Methods Patients who had undergone ACL reconstruction between April 2019 and February 2022 and those with intact ACL were eligible. Using magnetic resonance imaging, graft maturity was evaluated as the mean signal‐to‐noise quotient (SNQ) measured in three regions. Anterior tibial translation (ATT) was used to evaluate knee stability. Correlation analysis was conducted for the SIA, ATT, and clinical outcome scores. Multivariate stepwise regression analysis was used on the SIA and potential risk factors to determine their association with the graft SNQ. The SIA threshold of knee instability was calculated by receiver‐operating characteristic curves. Results Sixty‐three postoperative patients were enrolled. The SIA was significantly negatively associated with graft SNQ value. A multivariate stepwise regression analysis showed that SIA and body mass index were significant influencing factors associated with the graft SNQ. Correlations between the SIA and medial and lateral ATT were statistically significant. A larger SIA resulted in a decreased probability of medial and lateral ATT ≥ 5 mm. The SIA threshold of an increased risk of lateral ATT ≥ 5 mm was < 44.4°. A positive correlation was observed between SIA and subjective symptom subscales in the KOOS. Conclusions A low SIA is not conducive to graft maturation after ACL reconstruction. A larger graft SIA was correlated with better postoperative knee stability. However, the effect of the SIA on joint function was only significant in terms of symptoms. Therefore, these new findings provide new ideas for preoperative assessment and intraoperative determination of the ideal graft inclination.